A novel technique of friction aided deep drawing using a blank-holder divided into four segments - Hassan, M.A.; Takakura, N.; Yamaguchi, K. (2003)
A new process of friction aided deep drawing has been developed, in which the friction force between the blank and the blank-holder is used to aid the drawing deformation of the blank. This has been achieved by using a divided blank-holder, which consists of four segments and can move radially under axial pressure. The drawing process can be combined with a supplemental punch which gives a constant punch force during the drawing process. The experimental results show that there is no fracture at the flange of deformed blank, which is often observed in Maslennikov's process. The present new process is a very good trial to secure the advantages of deep drawing with elastic tools, but by using rigid tools. Very deep cups can be produced by repeating the drawing process. Theoretical analysis based on the energy and slab methods has also been conducted to study the possibility and the main features of this new process. (C) 2003 Elsevier Science B.V. All rights reserved.